FABRICATION OF COMBINED PROSTHESIS WITH CASTABLE EXTRACORONAL ATTACHMENTS (LABORATORY PROCEDURE) - Wahjuni, Sri; Mandanie, Sefy Ayu (Faculty of Vocational Studies, Universitas Airlangga, 2017)
Background: Nows a days has developed many kind of dentures to improve the functionality, comfort aesthetics. Stability, retention and its aesthetic can be improved by attachments. With many kind design assortment of dentures so need a different technique with the existing design. Purpose: The aim of this study is to know the danture manufacturing process in combination with Castable protesa Extracoronal Attachments labolatory procedure. Review: Fixed dentures are each bonded teeth protesa, inserted mechanically and support by teeth or dental implant abutment or that provide the main support for the dental protesa. A partial denture is a spin-off protesa that replaces one or more missing teeth, on the maxillary or mandibullary and can be opened by patients without the supervision of a dentist. Extracoronal attachment is an attachment that is part of the male and female part are almost entirely outside the contours of the Crown of the tooth. Conclusion: the initial stages are making of coping use wax pattern and inserted the female, the casting of metal, porcelain applications, making the wax pattern of the metal frame work, the casting of metal, inserted male, making a removable dentures.